PERLINDUNGAN HUKUM KONSUMEN DALAM PEMBELIAN SUATU BARANG DENGAN PENCANTUMAN KLAUSULA EKSONERASI PADA NOTA PEMBAYARAN DITINJAU DARI UNDANG – UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Soetijono , Irwan Kurniawan; Syaiful Bahri, Mohammad (Fakultas Hukum Universitas 17 Agustus 1945 Banyuwangi, 2023)
PROTECTION OF CONSUMER LEGAL PROTECTION IN PURCHASE OF AN GOODS BY INCLUDING AN EXONERATION CLAUSE ON PAYMENT NOTES REVIEWED FROM LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION(Case Study in Stores and Minimarkets in Banyuwangi Regency). The Exoneration Clause is a provision in an agreement where it is determined that there is a limitation or exemption from certain responsibilities, which normally according to law should be his responsibility. Exoneration clauses whose contents aim to transfer the responsibility of business actors are included in the type of standard clauses that are prohibited according to Law Number 8 of 1999 concerning Consumer Protection. The problems examined in this study include: 1) The legal consequences if the Payment Note includes an Exoneration Clause, 2) Legal Protection for Consumers regarding the application of the Exoneration Clause to Payment Notes. The research method used in this study is empirical juridical, namely legal research regarding the application of every legal event that occurs in society or direct research into the field using the methods of observation, interviews, documentation and then data analysis.The results of the study stated that: 1) Business actors violated the provisions for including the exoneration clause which had been stipulated, according to the Civil Code Articles (1320 and 1338) would be declared null and void, Article 62 paragraph (1) of the Consumer Protection Act already contains sanctions, namely threats of punishment maximum imprisonment of 5 (five) years or a maximum fine of Rp. 2,000,000,000.00 (two billion rupiah). 2) Legal protection for consumers is based on the existence of a number of consumer rights that need to be protected from actions that might harm consumers. Based on Article 1 of Law No. 8 of 1999 concerning Consumer Protection, which explains that consumer protection is all efforts to ensure legal certainty, however, in practice there are still many business actors who use exoneration clauses and this results in consumers not being protected.